Reasons for the high stability of nano-structured (La,Sr)MnO3 infiltrated Y2O3–ZrO2 composite oxygen electrodes of solid oxide electrolysis cells - Chen, Kongfa; Ai, Na; Jiang, San Ping (Elsevier Inc., 2012)
Nano-structured (La,Sr)MnO3 infiltrated Y2O3–ZrO2 (LSM–YSZ) oxygen electrodes show excellent activity and performance stability under solid oxide electrolysis cells (SOECs) operation conditions. LSM–YSZ composite electrodes are prepared by infiltrating pre-sintered YSZ scaffold with LSM nitrate solution, followed by heat-treatment at 900 or 1100 °C. The electrodes heat-treated at 900 °C exhibit an electrode polarization resistance as low as 0.21 Ω cm2 at 800 °C and are relatively stable under electrolysis operation at 500 mA cm− 2 for 100 h, while the electrodes heat-treated at 1100 °C show the increased stability with the electrolysis polarization. The results clearly indicate that LSM lattice shrinkage under anodic electrolysis conditions inhibits the agglomeration and grain growth of infiltrated LSM nanoparticles, leading to the highly stable nano-structured LSM–YSZ electrode structure.